The Influence Of Independence, Integrity, And Professionalism On Audit Judgement (Study At BPK RI Representative Of Bali Province) - Ramadhani, Muhamad Ivo Nizar; Suryanawa, I Ketut; Sudirga, I Gusti Ayu Desni Saraswati (Jurnal Ekonomi, 2024)
Management of state finances is one of the things that is very important for the economic life of a country. The BPK is a state institution that is free and independent in examining the management and responsibility of state finances. This research aims to obtain evidence regarding the influence of independence, integrity and professionalism on audit judgment. The data collection method is by distributing questionnaires to the BPK RI Bali Province Representative. The sampling method was non-probability sampling with a saturated sampling technique, so that a sample of 95 auditors was obtained. The analysis technique used is multiple linear regression analysis. The research results show that independence, integrity and professionalism have a positive effect on audit judgment.